Surgery for acute gallbladder disease in Sweden 1989–2006 – a register study. (April 2013) - Sandzén, Birger; Haapamäki, Markku M.; Nilsson, Erik; Stenlund, Hans C.; Öman, Mikael
Abstract Objective. Since early 1970s, prospective randomized controlled trials have emphasized the advantages of early cholecystectomy in patients with acute cholecystitis, compared to elective delayed cholecystectomy. The aim of this investigation was to study surgery for acute gallbladder disease in Sweden during a 15-year period when open cholecystectomy was replaced by a laparoscopic procedure. Material and methods. Data from the Swedish National Patient Register and the Cause of Death Register 1988–2006 comprising hospital stays with a primary diagnosis of gallbladder/gallstone disease in Sweden were retrieved. Patients were analyzed with reference to timing of cholecystectomy, length of hospital stay, and mortality. Results. Emergency cholecystectomy at index (first) admission or at readmission within 2 years of index admission was performed in 32.2% and 6.1% of patients, respectively. Elective cholecystectomy within 2 years of index admission was performed in 20.3% patients, whereas 41.3% of all patients did not undergo cholecystectomy within 2 years. Standardized mortality ratio did not significantly change during the audit period. Total hospital stay (days at index stay and subsequent stay(s) for biliary diagnoses within 2 years) was shorter for patients who had emergency cholecystectomy at first admission compared to patients with later or no cholecystectomy within 2 years. Conclusions. Around 30% of patients with acute gallbladder disease were operated with cholecystectomy during the first admission with no time trend from 1990 through 2004. A total of 40% of patients with acute gallbladder disease were not cholecystectomized within 2 years. Analysis of outcome of long-term conservative treatment is warranted.